2012
DOI: 10.1353/hpu.2012.0056
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autism Spectrum Disorder among Nigerian Children with Intellectual Disability: A Stopgap Assessment

Abstract: The prevalence of autism spectrum disorder (ASD) among sub-Saharan African children with intellectual disability is about 0.7% more than three decades ago. During this period, the prevalence of ASD has been on the increase worldwide. Studies are not available in recent times addressing epidemiology of ASD among sub-Saharan African children. The present study assessed the prevalence of ASD among Nigerian children with intellectual disability. Forty four children with intellectual disability were assessed for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…A few studies have attempted to estimate the burden of ASD in SSA [17, 19]. However, most of these studies used convenience sampling with data largely from hospital and specialist units for children with special needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have attempted to estimate the burden of ASD in SSA [17, 19]. However, most of these studies used convenience sampling with data largely from hospital and specialist units for children with special needs.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies reported higher prevalence among boys compared to girls. Bakare et al [19] in a study from Nigeria reported an ASD ratio of 4 : 1 for boys and girls, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…ASD was first identified in Nigeria in the 1970s (Franz et al, 2017). Despite this, prevalence rates for the condition remain uncertain (Bakare et al, 2012). A study by Bakare and Munir (2011b) suggested a prevalence rate of 0.08%, acknowledging that this may be artificially low due to the very limited attendance of children at clinics for childhood developmental disorders.…”
Section: Asd In Nigeriamentioning
confidence: 99%
“…The apparent increase in prevalence of autism has been attributed to the fact that diagnostic criteria for autism have evolved and broadened, parents and teachers have a greater level of awareness which has aided earlier and more accurate diagnosis, and the increased availability of services is also believed to aid the frequency of diagnosis of autism [9,10]. Bakare and colleagues [11] reported a prevalence of 11.4% for autism in a cohort of Nigerian children with intellectual disability, while the prevalence of autistic spectrum disorders (ASD) among children with developmental disorders in Egypt and Tunisia was reported as 33.6% and 11.5%, respectively [12]. There are very few reports on autism in Nigerian children and a dearth of literature addressing the epidemiology of ASD in African children.…”
Section: Introductionmentioning
confidence: 99%